Neoliberalização da prevenção do HIV/AIDS no Brasil e seus rebatimentos nas experiências de homens gays com o sexo e a sexualidade - Cristiano, Gabriela Dutra (2023)
This thesis aims to investigate the implications of the current official preventive model of HIV/Aids in the experiences of gay men with sex and sexuality in neoliberal terms in Brazil, with a view to helping on policy formulations that are more consistent with the needs and desires of this population. For this, we analyzed the conceptions that underlie the current preventive official model, how the "gay man" is built by politics and how he is built in the dialectical relationship with this policy, in addition to the rebuttals of this model in the experience of gay men with sex and sexuality. This is a qualitative research, of explanatory level, which at times assumes a more exploratory character. It is based on dialectical-critical materialism, from the perspective of what has been called neomarxism, while incorporating concepts and notions of other philosophical and theoretical currents. The discursive textual analysis (MORAES and GALIAZZI 2007) was adopted as a method to examine the data and to move the interpretations that were woven from the triangulation (TRIVIÑOS, 1987) of elements of the context (dependent capitalism, colonialism and neoliberalism) environment productions (documents produced for the prevention policy) and narrative of the subjects (interviews with gay men). Five publications of the Ministry of Health that deal with the current preventive model and 18 recorded and transcribed interviews were analyzed. The interviewees were invited to participate in the research from the snowball technique and the creation of a researcher profile in Grindr. The results show that the flexibility of neoliberal rationality allows it to enter the policy of HIV/Aids prevention in order to incorporate models claimed by civil society, learning made throughout the social history of the epidemic and the fetishizing narrative about freedom and possibilities.The conceptions that underlie the current preventive oficial model, Combined Prevention, build a complex and sophisticated discursive system, articulating intervention based on human rights and structural needs, with na individualizing perspective that makes subjects themselves responsible for their care. The current model advances in relation to the normative narrative about the condom by making available and proposing the combination of different resources and prevention strategies. The expansion of alternatives for safer sex produces relief from the trauma that the epidemic represented to the sociability of gay men as a social group. Although HIV still acts as a marker for sexual hierarchies, other bioidentities and differentiations constitute this process: bareback, undetectable, 11 PrEP user, for example. On the other hand, the way politics articulates today, the gay man becomes an entrepreneur of his own care. He needs to watch over himself and others, and is expected to be a rational, well-informed individual who manages his own risk. Although effectively none of the men correspond to this expectation, when it is not met, feelings such as frustration, surprise and guilt appear. Then, it is evidente that control strategies used by the State as a physical or mental pathologization, today coexist with other more sophisticated of neoliberal pharmacopornographic capitalism: they are medicated bodies, bodies that have sex, incorporated in the logic of the market as subjects responsible for themselves. It is concluded that the conceptions of autonomy and freedom, central to the current model, are in dispute and that it is necessary to rescue alternatives present in the critical perspective of human rights, health promotion and popular education.